When Are Nudges Desirable? Benefit Validity When Preferences Are Not Consistently Revealed. (14th November 2019) - Weimer, David L.
Abstract: Cost‐benefit analysis, as a tool of general use in policy analysis or as a mandated analytical process in some rulemaking, provides protocols for assessing the relative efficiency of policy alternatives. However, inconsistent and apparently irrational decisions by consumers in some situations call into question the validity of inferring the values that consumers place on outcomes from their observed choices. It also opens the door for "nudges" that change the architecture of choice to promote more "rational" consumer choice. Differences between decision utility and experience utility and the willingness of consumers to pay for reductions in temptation provide conceptual bases for thinking about the efficiency of nudges. However, assessment of nudges and their role in behavioral public administration should also recognize that heterogeneous preferences can result in increases in utility for some and decreases for others. Therefore, nudges require systematic assessment like other policy instruments .